Factors associated to quality of life among elderly with knee osteoarthritis (Fisioterapia e Pesquisa, 2008)
This study inquired whether quality of life (QoL) among elderly patients with knee osteoarthritis (OA) may be influenced by sociodemographic and/or clinic and functional factors. A sample of 40 elderly outpatients from a gerontological rehabilitation service in Sao Paulo answered the Brazilian version of the 36-Item Short Form Survey (SF-36). Functionality, joint stiffness and pain were assessed by the Womac - Western Ontario and MacMaster Universities Osteoarthritis Index. Further data on sociodemographic and clinical features, including pain-relieving strategies, were obtained by a complementary questionnaire. By means of linear regression analysis, an independent relationship was found between the Womac functionality domain and six SF-36 domains (p